(untitled) (2009)
: 1- . 2- . 3- . 4- . : : 1- . 2- . 3- . 4- . 500 17 . : 1- : . 2- : . 3- : . 4- : . 5- () : ( ). . 6- () : ( ). . 7- () : ( ). . 8- () : ( ).
Keywords: Education Islamique; Islamic Education; L accomplissement des étudiants; L enseignement du fait religieux; Religion education; Students achievement